Maternal Depression Implications for Systems Serving Mother and Child - Sontag-Padilla, Lisa M. (RAND Corporation, 2013)
Research indicates women are almost twice as likely as men to experience depression, and given that the majority of women age 15 to 50 have children, maternal depression is an important, potentially costly issue. RAND examined evidence on the impact of maternal depression as it relates to the public sector systems that serve mothers and children; specifically, public assistance, physical health, early intervention, education, and child welfare.